Reprieve Instead of Death (in Trials of Gypsies in Bohemia in the First Half of the 18th Century) or how not to Count History - Himl, Pavel (Dějiny – teorie – kritika, 2024)
This article is concerned with the persecution of Gypsies in Bohemia in the first third of the 18th century. As in other European countries, in cases where Gypsies had been already formally expelled from a land, Gypsy vagabondage was defined and punished as a capital crime. The article does not forget this normative aspect of the theme, but it nonetheless concentrates on the actual practice of persecution and above all on cases in which condemned Gypsies begged for mercy and their death penalty was in fact reduced to a more moderate punishment. The author also looks at the extensive powers of reprieve that the Prague Apellate Court (in the case of Gypsy vagabondage the tribunal of first instance), was granted by the ruler in the 1720s. Condemned Gypsies were not explicitly mentioned in this context, but there is plenty of evidence that they were not excluded from this practice of reprieve. The article criticises the view of the persecution of Gypsies that is based solely on the quantification of incomplete data in the manuals of condemnation of the Apellate Court. These books not only fail to indicate when the condemned were later reprieved, but also do not allow us to reliably identify individuals condemned. There are examples of one person appearing several times in them, sometimes under different names. It is this misleading quantified evidence that has helped give rise to the idea that the persecution of Gypsies in the early modern period was the first stage of the Gypsy Holocaust ini the 20th century. The article argues, on the contrary, that in relation to persecution the pre-modern differed from the modern state not only in terms of capacity, but fundamentally.